Clan Identity as a Determinant in the 2024 Regional Elections Among the Mandailing Community in Simangambat District - Meilinda Sariani Daulay; Hasan Asari (Journal of General Education and Humanities, 2026)
This study aims to analyse the role of clan identity in shaping the political preferences and orientations of the Mandailing community in the 2024 Regional Head Elections. The study employs a descriptive qualitative approach with data collection techniques including participatory observation, in-depth interviews, and documentation. The research informants consist of traditional leaders, religious leaders, youth figures, women, and the general public from various clans in Simangambat District. The results of the study indicate that clan identity continues to function as strong social and cultural capital in building solidarity, social legitimacy, and political loyalty. Regional head candidates use clan networks, participation in traditional activities, and cultural symbols and narratives as electoral strategies. However, there has been a shift in political orientation among young people and the educated community, who are beginning to prioritise rational considerations such as candidates' integrity, vision, and work programs. This study confirms that Mandailing local politics is in a transitional phase, moving from the dominance of genealogical identity politics to more rational political participation within the framework of modern democracy.